2022
DOI: 10.1155/2022/4910777
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and Biomedical Applications of Zirconium Nanoparticles: Advanced Leaps and Bounds in the Recent Past

Abstract: Many synthetic routes manufacture zirconium nanoparticles in metal oxide, nitride, and other combination forms. Coupled with other variables such as concentration, pH, and form of precursor used, the various synthetic methods support synthesizing the zirconium metal oxide nanoparticles with changed features. Various synthetic methods were studied, such as sol-gel, hydrothermal, laser ablation, and precipitation. All have different synthetic routes, different precursors and solvents were sued, and the product w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…ZrO 2 nanostructures have been widely investigated for their biocompatibility and potential use in biomedical applications [23,67]. Studies have demonstrated that ZrO 2 nanostructures exhibit low cytotoxicity, making them suitable for use in biomedical applications [102,109].…”
Section: Discussion Of the Biocompatibility And Toxicity Of Zro 2 Nan...mentioning
confidence: 99%
See 2 more Smart Citations
“…ZrO 2 nanostructures have been widely investigated for their biocompatibility and potential use in biomedical applications [23,67]. Studies have demonstrated that ZrO 2 nanostructures exhibit low cytotoxicity, making them suitable for use in biomedical applications [102,109].…”
Section: Discussion Of the Biocompatibility And Toxicity Of Zro 2 Nan...mentioning
confidence: 99%
“…Zirconia (ZrO 2 ) is a versatile material that has found numerous applications in various fields, including drug delivery, due to its physicochemical properties [65]. ZrO 2 nanostructures can be produced by several techniques, such as sol-gel, hydrothermal, and microwave-assisted synthesis [66][67][68][69][70][71] (Figure 2).…”
Section: Overview Of Zro 2 Nanostructure Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its many advantages, including its outstanding fracture toughness, high tensile strength, and hardness, zirconium nanoparticles have been employed in various syntheses. Five distinct isotopes of zirconium may exist naturally; out of those five, 90Zr is the most prevalent by a large margin (nearly 51.4%) [ 95 ].…”
Section: Importance Of Zirconium Nanoparticlesmentioning
confidence: 99%
“…[8] Other techniques such as Solgel often suffer from shortcomings such as shrinkage during gelation followed by subsequent drying process, prolonged sintering time with undesirable organic contaminants. [10,11] Similarly, hydrothermal synthesis is another popular technique performed at high pressure and moderate temperature, [12] but low product yield is the major concern despite their high purity. Hence, herein we adopted the coprecipitation method for Zirconia nanoparticle synthesis.…”
Section: Doi: 101002/crat202300160mentioning
confidence: 99%